Motion-Induced Scotoma. (February 2019) - Seizova-Cajic, Tatjana; Adamian, Nika; Duyck, Marianne; Cavanagh, Patrick
We investigated artificial scotomas created when a moving object instantaneously crossed a gap, jumping ahead and continuing its otherwise smooth motion. Gaps of up to 5.1 degrees of visual angle, presented at 18° eccentricity, either closed completely or appeared much shorter than when the same gap was crossed by two-point apparent motion, or crossed more slowly, mimicking occlusion. Prolonged exposure to motion trajectories with a gap in most cases led to further shrinking of the gap. The same gap-shrinking effect has previously been observed in touch. In both sensory modalities, it implicates facilitation among codirectional local motion detectors and motion neurons with receptive fields larger than the gap. Unlike stimuli that simply deprive a receptor surface of input, suggesting it is insentient, our motion pattern skips a section in a manner that suggests a portion of the receptor surface has been excised, and the remaining portions stitched back together. This makes it a potentially useful tool in the experimental study of plasticity in sensory maps.